2008
DOI: 10.1161/strokeaha.107.505438
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With a High Risk of Recurrence in Patients With Transient Ischemic Attack or Minor Stroke

Abstract: Background and Purpose-The aim of our study was to identify factors associated with stroke recurrence after an initial minor stroke or transient ischemic attack (TIA) in a prospective hospital-series. Methods-Included in the series were 689 patients with NIHSS lower than 4 at hospital admission. The end point was a new neurological event (worsening Ն4 points in the initial NIHSS was considered as recurrence) at 90 days (and additionally at 7 days). Factors based on two previous reported scores (ABCD and SPI-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
102
5
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(123 citation statements)
references
References 35 publications
8
102
5
8
Order By: Relevance
“…Recurrence of IS was defined as a new focal neurological deficit of vascular origin lasting >24 hours and without hemorrhage on computed tomography or MRI of the brain. 12 At 3, 6, and 12 months after discharge, patients or their relatives were contacted over the telephone by trained research personnel at Beijing Tian Tan hospital and were asked whether patients had new symptoms or hospitalized again with another stroke. All recurrence or progressive deterioration of IS was verified at the index hospitals based on the NIHSS score and the presence of new neurological deficits documented in the medical records in combination with computed tomography or MRI images.…”
Section: Follow-up and Clinical Outcome Evaluationsmentioning
confidence: 99%
“…Recurrence of IS was defined as a new focal neurological deficit of vascular origin lasting >24 hours and without hemorrhage on computed tomography or MRI of the brain. 12 At 3, 6, and 12 months after discharge, patients or their relatives were contacted over the telephone by trained research personnel at Beijing Tian Tan hospital and were asked whether patients had new symptoms or hospitalized again with another stroke. All recurrence or progressive deterioration of IS was verified at the index hospitals based on the NIHSS score and the presence of new neurological deficits documented in the medical records in combination with computed tomography or MRI images.…”
Section: Follow-up and Clinical Outcome Evaluationsmentioning
confidence: 99%
“…However, TIA patients are a heterogeneous group in terms of symptoms, risk factors, underlying pathology, and early prognosis. 3 The presence of large-artery atherosclerosis (LAA) has been the main established predictor of subsequent stroke [4][5][6] so far, but a definitive prognostic tool for stroke recurrence (SR) is not defined.…”
mentioning
confidence: 99%
“…[4][5][6] We evaluated metabolomic profiles of patients with symptomatic carotid or intracranial stenosis of at least 50%. The results (figure 1E) revealed that metabolomic profiles are able to offer a high accuracy predicting presence of LAA (PLS-DA accuracy 91%-98%, positive: specificity 5 0.79, sensitivity 5 1; negative: specificity 5 0.86, sensitivity 5 1; dataset 1).…”
mentioning
confidence: 99%
“…Factors associated with a high risk of recurrence in patients with TIA or minor stroke were different from those of general stroke16; however, data from previous studies were derived from trials or cohorts in which patients were recruited weeks or months after their initial event and underestimated early recurrence, especially for minor stroke or TIA 8, 9, 17. Consequently, the risks of recurrent stroke caused by METS and DM in patients with a minor stroke or TIA should be further examined.…”
Section: Introductionmentioning
confidence: 99%